PEMAHAMAN MODEL PROJECT BASED LEARNING SEBAGAI KESIAPAN PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) OLEH ANGKATAN 2019 PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Deswantri Ramadhani; Merri Silvia Basri; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Teaching and learning activities are activities that determine success in achieving educational goals. One of the general functions and objectives of learning in schools is the readiness of teachers in providing teaching that can develop abilities to students through the selection of learning models. The Project-based Learning (PjBL) learning model is based on the characteristics of this learning model itself which focuses on the central role of students in carrying out learning activities. The benefits of the project-based learning model (Project-based Learning) are beneficial for the development of students' creativity. The purpose of this research is to raise students' awareness that students need to implement Project-based Learning because it is very much needed in schools and to find out the Understanding of Project-based Learning Models as readiness for School Field Introduction (PLP) Students of the Class of 2019 Japanese Language Education, Riau University. The type of research used is the type of mixed research (mixed methods). The instruments used in this study were observation sheets, interviews, and students' ability to make projects using the Project-based Learning model which was distributed directly to class 2019 students. 26 Japanese Language Education Students Class of 2019 in understanding the Project-based Learning model which stated that the average value of 86.615% was included in the